The London money market and non-British bank lending during the first globalisation: evidence from Brazil - Kisling, W; Molteni, M (Springer, 2024)
This study examines the relationship between the London money market (LMM) and the credit provision of non-British overseas banks in peripheral economies during the first wave of globalisation. Using monthly data between 1889 and 1913, we find a positive relationship between the amount of credit authorised by the German Brasilianische Bank für Deutschland in Brazil and the spread between the London market and floating rate. Our results suggest that increased demand for foreign bills and/or decreased borrowing costs in the LMM leads to an increase in credit supply. We use the impact of annual tax payments on the spread between the market and floating rate as an instrumental variable (IV) to show that this relationship is causal. Although there is a significant amount of literature on London’s historic role as a global financial centre and a growing number of studies on foreign banking history, little quantitative evidence is available about the connection between the two. This study bridges this gap.